CK2α-mediated phosphorylation of GRP94 facilitates the metastatic cascade in triple-negative breast cancer - Hye-Youn Kim; Young-Mi Kim; Suntaek Hong (Cell Death Discovery)
Abstract Distant metastasis is a significant hallmark affecting to the high death rate of patients with triple-negative breast cancer (TNBC). Thus, it is crucial to identify and develop new therapeutic strategies to hinder cancer metastasis. While emerging studies have hinted a pivotal role of glucose-regulated protein 94 (GRP94) in tumorigenesis, the exact biological functions and molecular mechanisms of GRP94 in modulating cancer metastasis remain to be elucidated. Our study demonstrated an increased expression of GRP94 in TNBC correlated with metastatic progression and unfavorable prognosis in patients. Functionally, we identified that GRP94 depletion significantly diminished TNBC tumorigenesis and subsequent lung metastasis. In contrast, GRP94 overexpression exacerbated the invasiveness, migration, and lung metastasis of non-TNBC cells. Mechanistically, we found that casein kinase 2 alpha (CK2α) active in advanced breast cancer phosphorylated GRP94 at a conserved serine 306 (S306) residue. This phosphorylation increased the stability of GRP94 and enhanced its interaction with LRP6, leading to activation of canonical Wnt signaling. From a therapeutic standpoint, we found that benzamidine, a novel CK2α inhibitor, effectively suppressed GRP94 phosphorylation, LRP6 stabilization, and metastasis of TNBC. Our results point to the critical role of CK2α-mediated GRP94 phosphorylation in TNBC metastasis through activation of Wnt signaling, highlighting GRP94 as a therapeutic target to impede TNBC metastasis.